The brittle-to-ductile transition in cold-rolled tungsten sheets: Contributions of grain and subgrain boundaries to the enhanced ductility after pre-deformation. (December 2020) - Bonnekoh, Carsten; Lied, Philipp; Zaefferer, Stefan; Jäntsch, Ute; Hoffmann, Andreas; Reiser, Jens; Rieth, Michael
Highlights: In cold-rolled W, a striking fraction of straight dislocations spans across the grains. These segments are presumably ½〈111〉 screw type and the result of rolling below the knee temperature. The contributions of CSL boundaries to the reduction in BDT temperature seems negligible. Hall–Petch-like attempts describe the rolling-induced reduction in BDT temperature. Considering LABs and HABs instead of HABs only results in more promising correlations. Abstract: One of the key demands on tungsten (W) as designated plasma-facing material (PFM) is the capability to fulfill a structural function. Since W has refused ductilization strategies by alloying alone, the production of W materials with enhanced ductility has come into focus considering tailored microstructures. This work addresses the rolling-induced microstructural modifications of warm- and cold-deformed W sheets and is supplemented by a comprehensive fracture mechanical study as a fundament for correlations between the spatial distribution of boundaries and brittle-to-ductile transition (BDT) temperature. Here we show that an extended Hall–Petch-like relationship is well suited to describe the rolling-induced reduction in BDT temperature and moreover has the potential to reflect the anisotropic nature of the transition temperature in severely rolled W sheets. Using the data of warm- and cold-rolled W sheets and also of strongly recovered W, best description of the BDT temperature was achieved by using as microstructural variables (i) the mean spacing between boundaries which intersect with the crack front and (ii) the mean boundary spacing along the normal of the crack plane. Taking into account the similarity to recent simulative-derived relationships, our findings support the theory suggesting the stimulated dislocation nucleation at boundaries as the decisive factor for more effective shielding of the crack tip in UFG materials and, in consequence, significantly reduced BDT temperatures. Besides, this work gives strong indications that the reduction of the BDT temperature in UFG W is not related to coincidence site lattice (CSL) boundaries.